PENGGUNAAN GEOGEBRA DALAM MENGEMBANGKAN KEMAMPUAN VISUAL THINKING MATEMATIS SISWA PADA PEMBELAJARAN MATEMATIKA SECARA DARING [USING GEOGEBRA TO DEVELOP STUDENTS’ MATHEMATICAL VISUAL THINKING ABILITY IN ONLINE MATHEMATICS LEARNING] - Subakti, Mega Prana; Listiani, Tanti (Universitas Pelita Harapan, 2022)
Mathematics is a subject which uses mathematical symbols, such as numbers and graphs, that some students find difficult to learn. To understand it, mathematical visual thinking skills are needed. In one of the schools in Kupang, the students’ mathematical visual thinking ability is low. Many students cannot represent problems with mathematical symbols. To solve this, the teacher uses GeoGebra as a teaching aid. GeoGebra is a software program that has many advantages as a tool for learning mathematics. GeoGebra can be used effectively with the various features it has. The purpose of this research is to describe how to use GeoGebra and what features can be used in GeoGebra to develop mathematical visual thinking abilities. This research was conducted in grade 10 at one of the schools in the city of Kupang. The method of this reseacrh is qualitative descriptive. The result of this research is that there are several GeoGebra features that can help learning, including point, line, algebra input, and pen. These features can be used easily by just clicking on or writing according to the instructions on the GeoGebra page. The implication of this research is that teachers still have to teach students how to use this tool wisely so that its advantages can be maximally utilized, moreover, they can glorify God through using GeoGebra. The conclusion is that GeoGebra is a tool that can help in developing mathematical visual thinking abilities because its features can enable indicators of mathematical visual thinking abilities.BAHASA INDONESIA ABSTRACT: Matematika merupakan mata pelajaran yang identik dengan simbol-simbol matematis seperti angka-angka hingga grafik-grafik yang bisa membuat siswa merasa kesulitan. Untuk memahaminya, dibutuhkan kemampuan visual thinking matematis. Namun masalah yang terjadi pada salah satu sekolah di Kupang, kemampuan visual thinking matematis siswa masih kurang. Banyak dari siswa yang tidak bisa merepresentasikan persoalan-persoalan ke dalam simbol matematis. Untuk memecahkan masalah tersebut, guru menggunakan GeoGebra sebagai media pembelajaran. GeoGebra merupakan aplikasi yang punya banyak kelebihan dalam membantu pembelajaran matematika. GeoGebra dapat digunakan secara efektif dengan berbagai fitur yang dimilikinya. Tujuan penulisan ini adalah untuk mendeskripsikan bagaimana cara menggunakan GeoGebra dan apa saja fitur yang dapat digunakan dalam GeoGebra untuk mengembangkan kemampuan visual thinking matematis.Penelitian ini dilakukan di kelas X pada salah satu sekolah yang ada di kota Kupang Penulisan ini menggunakan metode deskriptif kualitatif. Hasil penulisan ini adalah ada beberapa fitur-fitur yang dapat membantu pembelajaran, di antaranya adalah point, line, input algebra, dan pen. Implikasi penelitian ini yaitu guru tetap harus mengajarkan kepada siswa agar dapat menggunakannya dengan bijak sehingga dapat dimanfaatkan secara maksimal, bahkan dapat memuliakan Allah melalui GeoGebra. Kesimpulannya adalah GeoGebra merupakan alat yang dapat membantu dalam mengembangkan kemampuan visual thinking matematis, karena fitur yang dimilikinya dapat mengampu setiap indikator visual thinking matematis.